Twister [videorecording (DVD)] - Bont, Jan de; Hunt, Helen, 1963-; Paxton, Bill; Gertz, Jami; Elwes, Cary, 1962-; Hoffman, Philip Seymour, 1967-2014 (Distributed by Warner Home Video, 2009)
A scientist is determined to discover a better way of predicting tornadoes with a device that shoots thousands of little trackers into the eye of the storm. Trouble is, getting it there is very dangerous.